Implications of Eocene-age Philippine Sea and forearc basalts for initiation and early history of the Izu-Bonin-Mariana arc. (1st May 2018) - Yogodzinski, Gene M.; Bizimis, Michael; Hickey-Vargas, Rosemary; McCarthy, Anders; Hocking, Benjamin D.; Savov, Ivan P.; Ishizuka, Osamu; Arculus, Richard
Abstract: Whole-rock isotope ratio (Hf, Nd, Pb, Sr) and trace element data for basement rocks at ocean drilling Sites U1438, 1201 and 447 immediately west of the KPR (Kyushu-Palau Ridge) are compared to those of FAB (forearc basalts) previously interpreted to be the initial products of IBM subduction volcanism. West-of-KPR basement basalts (drill sites U1438, 1201, 447) and FAB occupy the same Hf-Nd and Pb-Pb isotopic space and share distinctive source characteristics with εHf mostly > 16.5 and up to εHf = 19.8, which is more radiogenic than most Indian mid-ocean ridge basalts (MORB). Lead isotopic ratios are depleted, with 206 Pb/ 204 Pb = 17.8–18.8 accompanying relatively high 208 Pb/ 204 Pb, indicating an Indian-MORB source unlike that of West Philippine Basin plume basalts. Some Sr isotopes show affects of seawater alteration, but samples with 87 Sr/ 86 Sr < 0.7034 and εNd > 8.0 appear to preserve magmatic compositions and also indicate a common source for west-of-KPR basement and FAB. Trace element ratios resistant to seawater alteration (La/Yb, Lu/Hf, Zr/Nb, Sm/Nd) in west-of-KPR basement are generally more depleted than normal MORB and so also appear similar to FAB. At Site U1438, only andesite sills intruding sedimentary rocks overlying the basement have subduction-influenced geochemical characteristics (εNd ∼ 6.6, εHf ∼ 13.8, La/Yb > 2.5, Nd/Hf ∼ 9). The key characteristic that unites drill site basement rocks west of KPR and FAB is the nature of their source, which is more depleted in lithophile trace elements than average MORB but with Hf, Nd, and Pb isotope ratios that are common in MORB. The lithophile element-depleted nature of FAB has been linked to initiation of IBM subduction in the Eocene, but Sm-Nd model ages and errorchron relationships in Site U1438 basement indicate that the depleted character of the rocks is a regional characteristic that was produced well prior to the time of subduction initiation and persists today in the source of modern IBM arc volcanic rocks with Sm/Nd > 0.34 and εNd ∼ 9.0.